Effects of permeability and electric field on nonlinear Oberbeck Electro-convection in a vertical poorly conducting fluid saturated porous channel - Rudraiah, N.; Shashikala, B. S. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
The effects of permeability on nonlinear Oberbeck Electro-convection in a poorly conducting fluid saturated porous medium in a vertical channel, when the walls are held at different temperatures with temperature difference perpendicular to gravity, is studied using the modified Navier stokes equation in the presence of both induced and an applied electric field. Both analytical and numerical solutions for the non-linear coupled equations governing the motion are obtained and found that analytical solutions agree well with numerical solutions for values of the buoyancy parameter N